Optimasi Keluarga Peserta “Sekolah Rimbawan Kecil” di Sekitar Taman Nasional Gunung Halimun Salak - Resti Meilani; Endang Koestati Sriharini Muntasib; Brigita Laura Fatria (Institut Pertanian Bogor, 2015)
Sekolah Rimbawan Kecil (Serincil, literally means School of Little Forester) is nonformal conservation education for the children of Muara Kampong, Cibunian Village, Pamijahan Subdistrict, which is located adjacent to area of Gunung Halimun Salak National Park (GHSNP). The community of the kampong, including parents of Serincil children, relied on GHSNP area for their livelihood. Therefore, conservation education was also important for them to reduce their dependence on GHSNP area, and thus optimizing their role in conservation activities. Evaluation showed that the most intensive implementation of optimization subjects by the community was the one most suitable with their everyday life (dapur hidup/vegetable farming), while quite intensive on cattle health, and less intensive on poultry farming. Forest tree nursery should be a main priority to establish intensive cooperation between the community and GHSNP management.